My fair frauds [large type] - Kelly, Lee; Thorne, Jennifer, 1980- (Center Point Large Print, 2026)
"The Grand Duchess Marie Charlotte Antonie of Würrtemberg-a turmoil-plagued Germanic nation with closely guarded emerald mines-has taken Gilded Age high society by storm. Little does the upper crust know that Würrtemberg's mines are a sham and its "deposed duchess" is actually a con woman named Alice, a fallen woman out for revenge against the five ruthless robber barons who destroyed her father and left her family in shambles. Alice's long investment con finally clicks into place when she meets a scrappy magician's assistant named Cora, a drifter who has lofty aspirations of her own, a malleable young lady who proves the perfect debutante pawn to lure in Alice's final, and otherwise unattainable, target. With the help of insider and society maestro Ward McAllister, among others, Alice and Cora launch into the social season of 1884, scheming their way through grand balls, private dinners, and opera nights, ensnaring Alice's targets one by one. But as they hurtle toward their ultimate swindle, a sprawling orchestrated scheme at their fabricated embassy to rob their targets blind, pressures close in from all sides. Mutiny within the ranks, hidden moles, crises of conscience . . . This sting is sure to be the event of the season. Or else ruin Alice and Cora both."--